The Bacillus subtilis spoIIG operon encodes both sigma E and a gene necessary for sigma E activation. - Jonas, R M (1988)
A sporulation-specific sigma factor of Bacillus subtilis (sigma E) is formed by a proteolytic activation of a precursor protein (P31). Synthesis of the precursor protein is shown to be abolished in B. subtilis mutants with plasmid insertions as far as 940 base pairs upstream of the P31 structural gene (sigE), and processing of P31 to sigma E is blocked by a deletion in this upstream region. These results substantiate the view that sigE is the distal member of a 2-gene operon and demonstrate that the upstream gene (spoIIGA) is necessary for sigma E formation.